Development of Osmotically Controlled Oral Drug Delivery Systems of Tramadol Hydrochloride: Effect of Formulation Variables on In Vitro Release Kinetics - Nagaraj, B. (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: Numerous technologies have been used to control the systemic delivery of a pharmacologically active ingredient in a predetermined, predictable, and reproducible manner. One of the most interesting approaches is osmotically controlled oral drug delivery systems. By optimizing formulation and processing parameters, it is possible to develop osmotic systems to deliver drugs of diverse nature at a predetermined rate with high in vitro-in vivo correlation. The aim of the current study was to formulate elementary osmotic pump (EOP) device of freely water-soluble tramadol hydrochloride, a non-steroidal anti-inflammatory agent. Materials and Methods: Formulations were prepared by wet granulation method, coated with cellulose acetate (CA)/ethyl cellulose solution containing varying amounts of dibutylphthalate as a plasticizer. Drug release was studied using USP Type II apparatus. The effect of different formulation variables on drug release, namely, type and concentration of osmogen and plasticizer, size of the delivery orifice, nature of the rate controlling membrane, and membrane weight gain was studied. Results: The formulation containing mannitol in the drug:osmogen ratio of 1:0.5 and lactose in the ratio 1:0.25, and 1:0.5 (drug:osmogen) showed more than 80% of drug release in 6 h with zero-order release pattern. The 4% CA solution in acetone with dibutylphthalate (15% w/w of polymer), with orifice diameter 480 Î¼m, 565 Î¼m, and 8% increase in weight on coating, were found to control the drug release. Drug release from the developed formulations was found to be independent of pH and agitation intensity. The manufacturing procedure was reproducible, and formulations were stable upto 3 months as per ICH guidelines. Conclusion: EOPs and process parameters of tramadol hydrochloride were developed based on osmotic technology.